Two Sides of the Same Coin: Sustaining Loan‐Use Ambiguity in Microfinance through Harmonizing Practices - Vermeire, Jacob; Meuleman, Miguel; Lepoutre, Jan (Journal of Management Studies, 2026)
Abstract Despite its promise to alleviate poverty through entrepreneurship, microfinance is widely used for household purposes, challenging Western assumptions of microfinance as entrepreneurial finance and raising questions about the viability of microfinance organizations (MFOs). To understand how microfinance persists despite such use, we conducted an embedded case study of a South African MFO operating in a rural, resource‐constrained context shaped by Ubuntu – a communitarian ethic emphasizing relational interdependence and mutual care. Drawing on scarcity theory and a practice‐based view of financial resourcing, we show how scarcity is collectively navigated through culturally embedded practices that stabilize loan‐use ambiguity in everyday microfinance interactions. We find that loan officers and recipients jointly enact three harmonizing practices – reverence for repayment, empathic financial support, and entrepreneurial discretion – that sustain this ambiguity between the MFO's espoused entrepreneurial schema and enacted livelihood‐oriented practices. Through these practices, microfinance remains viable as a community‐embedded system of financial support, even as loan use departs from formal entrepreneurial prescriptions. By conceptualizing microfinance as a community‐embedded system of financial resourcing rather than a narrowly entrepreneurial intervention, this study contributes to research on microfinance, scarcity, and resourcing in communitarian settings.